The Importance of Agricultural Knowledge in Early Childhood Education: A Scoping Review - Fadlillah, M.; Oktavianingsih, Eka; Lisdayana, Nurmalisa; Latif, Muhammad Abdul (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2023)
Indonesia is an agrarian country and has potential in agriculture that is not in line with the potential of supporting human resources. Therefore, it is necessary to introduce agriculture from an early age. Early childhood learning programs with an agricultural perspective can equip children with knowledge about the importance of agriculture as well as basic skills such as caring for, watering and planting plants. This research aims to understand the importance of agriculture-based learning in early childhood education environments. This research method uses Preferred Reporting Items for Systematic Review and Meta-Analyze Extensions for scoping reviews using 3 databases namely science direct, google Scholar, and sage journals. The literature reviewed from the scoping review obtained 8 articles that fulfilled the use of qualitative and quantitative or mixed methods. The types of journals produced are mostly children's education journals, environmental education journals for children, and journals about nutrition for children. Many research subjects also center on children's intelligence, scientific and nature-friendly attitudes, cognitive, language, and social skills that children can acquire from gardening or agriculture-based learning. From data collection and preparation of literature material, benefits from agricultural-based learning programs are obtained. This benefit is the basis for the importance of agriculture-based learning in kindergarten children. The benefits of agricultural learning-based activities in Early Childhood Education (ECE) include increasing early childhood knowledge and love for agricultural activities, increasing children's naturalistic intelligence, promoting healthy food in early childhood, environmentally friendly attitudes, and cognitive intelligence.